Synergy between the KEAP1/NRF2 and PI3K Pathways Drives Non-Small-Cell Lung Cancer with an Altered Immune Microenvironment - Best, Sarah A; De Souza, David P; Kersbergen, Ariena; Policheni, Antonia N; Dayalan, Saravanan; Tull, Dedreia; Rathi, Vivek; Gray, Daniel H; Ritchie, Matthew E; McConville, Malcolm J; Sutherland, Kate D (Cell metabolism, 2018)
The lung presents a highly oxidative environment, which is tolerated through engagement of tightly controlled stress response pathways. A critical stress response mediator is the transcription factor nuclear factor erythroid-2-related factor 2 (NFE2L2/NRF2), which is negatively regulated by Kelch-like ECH-associated protein 1 (KEAP1). Alterations in the KEAP1/NRF2 pathway have been identified in 23% of lung adenocarcinomas, suggesting that deregulation of the pathway is a major cancer driver. We demonstrate that inactivation of Keap1 and Pten in the mouse lung promotes adenocarcinoma formation. Notably, metabolites identified in the plasma of Keap1 /Pten tumor-bearing mice indicate that tumorigenesis is associated with reprogramming of the pentose phosphate pathway. Furthermore, the immune milieu was dramatically changed by Keap1 and Pten deletion, and tumor regression was achieved utilizing immune checkpoint inhibition. Thus, our study highlights the ability to exploit both metabolic and immune characteristics in the detection and treatment of lung tumors harboring KEAP1/NRF2 pathway alterations.